2022
DOI: 10.1093/texcom/tgac028
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala subnuclei volumes, functional connectivity, and social–emotional outcomes in children born very preterm

Abstract: Children born very preterm can demonstrate social-cognitive impairments, which may result from limbic system dysfunction. Altered development of the subnuclei of the amygdala, stress-sensitive regions involved in emotional processing, may be a key predictor of social-skill development. In a prospective cohort study, 7-year-old children born very preterm underwent neurodevelopmental testing and brain MRI. The Child Behavioral Checklist (CBCL) was used to assess social–emotional outcomes. Subnucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Very preterm birth (VPT; i.e., at <33 weeks' gestation) occurs during a rapid stage of brain development, making those born VPT vulnerable to neurological insult (Volpe, 2009) and long-lasting difficulties in attention, executive function, and socio-emotional processing (Anderson et al, 2021;Johnson and Marlow, 2011;Kroll et al, 2017). Functional connectivity alterations in brain regions and networks important for cognitive and affective processing have also been reported in VPT samples across the lifespan, and have been studied amongst the possible biological mechanisms underlying the behavioural difficulties associated with VPT birth (Bäuml et al, 2015;Kanel et al, 2022;Mueller et al, 2022;Papini et al, 2016;Ramphal et al, 2020;Rogers et al, 2017;Siffredi et al, 2022;Sylvester et al, 2018). It is important to highlight, however, that not only have previous studies identified brain changes associated with behavioural difficulties in those born VPT, but have also characterised neural adaptions which support domain-specific performance (Daamen et al, 2014;Finke et al, 2015;Nosarti et al, 2006Nosarti et al, , 2009Schafer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Very preterm birth (VPT; i.e., at <33 weeks' gestation) occurs during a rapid stage of brain development, making those born VPT vulnerable to neurological insult (Volpe, 2009) and long-lasting difficulties in attention, executive function, and socio-emotional processing (Anderson et al, 2021;Johnson and Marlow, 2011;Kroll et al, 2017). Functional connectivity alterations in brain regions and networks important for cognitive and affective processing have also been reported in VPT samples across the lifespan, and have been studied amongst the possible biological mechanisms underlying the behavioural difficulties associated with VPT birth (Bäuml et al, 2015;Kanel et al, 2022;Mueller et al, 2022;Papini et al, 2016;Ramphal et al, 2020;Rogers et al, 2017;Siffredi et al, 2022;Sylvester et al, 2018). It is important to highlight, however, that not only have previous studies identified brain changes associated with behavioural difficulties in those born VPT, but have also characterised neural adaptions which support domain-specific performance (Daamen et al, 2014;Finke et al, 2015;Nosarti et al, 2006Nosarti et al, , 2009Schafer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…9 In VPT children and adults, increased and decreased FC of the amygdala with other brain regions including posterior cingulate cortex, precuneus, and superior temporal areas and thalamus have been associated with the capacity to recognize facial expression of anger and with social problems. 7,10,11 Similarly, static FC studies using whole-brain datadriven approaches have found atypical resting-state networks associated with prematurity across the lifespan, especially FC of the salience, default mode, and frontal networks. 6,12 In VPT children, Mossad et al 13 showed that increased connectivity in the default mode network at the age of 6 was linked to social and working memory difficulties by the age of 8.…”
mentioning
confidence: 99%
“…In VPT infants, overall cognitive scores at 6 months were predicted by medial prefrontal cortex‐executive control connectivity strength 9 . In VPT children and adults, increased and decreased FC of the amygdala with other brain regions including posterior cingulate cortex, precuneus, and superior temporal areas and thalamus have been associated with the capacity to recognize facial expression of anger and with social problems 7,10,11 . Similarly, static FC studies using whole‐brain data‐driven approaches have found atypical resting‐state networks associated with prematurity across the lifespan, especially FC of the salience, default mode, and frontal networks 6,12 .…”
mentioning
confidence: 99%
“…Changes in the function of this circuit seem to have an effect on how emotions are regulated and increase the risk of psychiatric disorders (VanTieghem and Tottenham 2018 ). For instance, greater exposure to pain-related stress in infants born low-risk preterm has been linked to disrupted developmental scores (Morag et al 2017 ).…”
mentioning
confidence: 99%